Efeitos da fadiga sobre a economia de pedalada e ativação muscular em ciclistas treinados durante teste e reteste de exaustão - Barbosa, Igor Martins (2021)
Fatigue is an inevitable process during intense and/or extensive exercises, which reduces the performance and efficiency of athletes in most sports, such as cycling. In addition, as the mechanisms of fatigue become more active, changes in the pattern of muscle activation may occur, especially in the muscles that have primary action to perform the movement, in this case the cycling. However, these reductions and alterations are not yet well understood, so that studying them over time in activity can help in understanding the mechanisms of fatigue that lead to exercise intolerance. From this, the objective of the present work was to verify the effect of fatigue on pedaling economy and muscle activation in trained cyclists during exhaustion test and retest. Sixteen competitive male cyclists were evaluated (age 23 ±7 years, body mass: 67 ±7 kg and height: 177 ±6 cm). The athletes had a training experience of ~6.5 years, a usual training volume of ~6 days/week and ~460 km/week. The cyclists made two visits to the laboratory, with the first visit performed an anthropometric evaluation and then an incremental test (heating to 100W for 10 minutes, followed by the addition of 25W every minute until exhaustion) in order to determine the maximum power. In the second visit, the cyclists performed a heating similar to the first visit, then performed the two tests of time until exhaustion at maximum and constant power, with a period of 10 minutes of recovery between tests. During the tests the myoelectric activation of RF, VL and MV was measured, as well as the gas exchange breath by breath. From this, the myoelectric activity was submitted to a frequency band technique, being represented values of total activation, high and low frequency for each muscle. While the gas exchange data were used to calculate the energy demand (PM) and efficiency (GE) of cyclists. The results found indicate reductions in GE and increase of PM in both tests until now intermediate, from which a plateau was established. As for EMG results, reductions in activation of the high frequency bands for the VL muscle were found during the tests, the MV showed reduction only in the second test, remaining stable in the first. While for RF there was an increase in activation throughout the first test and remained stable in the second test. For the low frequency bands, there was an increase in activation for all muscles evaluated during both tests. Finally, the full activation was not changed in both LV and MV, only for RF was there an increase throughout the tests.